Forms of Islamic Economics: Buying and Selling, Syirkah, Rahn, Classification of Contracts - Danis Oktafiana Sari (Escalate : Economics and Business Journal, 2026)
Islamic economics is an economic system based on the Qur'an and Sunnah that aims to realize justice, balance, and the benefit of individuals and society. In its implementation, every economic activity must be based on a valid contract in accordance with sharia principles, thereby avoiding practices containing elements of usury, gharar (uncertainty), and maisir (gambling). This article aims to examine various forms of transactions in Islamic economics, including buying and selling (al-bai'), syirkah, rahn, and the classification of contracts as a legal basis for muamalah activities. The article was written using a library research method by reviewing various sources, such as the Qur'an, hadith, Islamic economics books, fatwas of the National Sharia Council-Indonesian Ulema Council (DSN-MUI), and relevant scientific articles. The results of the study indicate that buying and selling is a form of transaction that is permitted as long as it meets the pillars and conditions stipulated by sharia. Syirkah is a form of business cooperation that applies the principles of profit sharing and fair risk sharing. Rahn serves as a debt collateral contract that provides protection for both parties without involving interest or usury. Meanwhile, the contract is a fundamental element that determines the validity of every Islamic economic transaction and can be classified based on its purpose, object, level of certainty of outcome, and legal validity. The application of various forms of Islamic economics is not only relevant in Islamic financial institutions, but also in modern business activities, digital commerce, and micro, small, and medium enterprises (MSMEs). Therefore, an understanding of the concepts of sale and purchase, syirkah, rahn, and the classification of contracts is expected to enhance the more effective application of Islamic economic principles in supporting fair, transparent, and sustainable economic development.